Effect of mineral dust aerosol aspect ratio on polarized reflectance. (January 2015) - Huang, Xin; Yang, Ping; Kattawar, George; Liou, Kuo-Nan
Abstract: The effects of dust particle aspect ratios on single- and multiple-scattering processes are studied using the spheroidal model in order to obtain a better understanding of the radiance and polarization signals at the top of the atmosphere (TOA) under various dust-aerosol-loading conditions. Specifically, the impact of the particle aspect ratio on the polarization state of the TOA radiation field is demonstrated by comparing the normalized polarized radiances observed by the POLDER (POLarization and Directionality of the Earth׳s Reflectances) instrument on board the PARASOL (Polarisation et Anisotropie des Reflectances au sommet de l׳Atmosphère, couples avec un Satellite d׳Observation emportant un Lidar) satellite with the corresponding theoretical counterparts. Furthermore, presented are the aspect ratio values inferred from multi-angular polarized radiance measurements of Saharan and Asian dust by the POLDER/PARASOL. Highlights: The radiative effect of dust aerosol aspect ratio is investigated. A computational efficient vector radiative transfer model is developed. Spaceborne Polarimetric measurements are used to retrieve aerosol properties. A case study of Saharan dust shows a mean aspect ratio of 2.5. Asian dust exhibits two aspect ratio values, 2.5 and 1.25.